BIOPRODUCTIVITY OF TYPICAL CHERNOZEM DEPENDING ON THE ACTION, THE AFTEREFFECT OF FERTILIZERS ON HUMUS STATE IN AGROCENOSES - Глущенко, Л. Д.; Гангур, В. В. (Scientific Progress & Innovations, 2013)
Long duration application of the different systems of fertilizer and basic till of soil of typical black soil resulted in differentiation of the ground cover at the level of gumus and bioproductivity. Applying of manure –10 t/ha – on a background of N52R52K52, with the combined system of basic till of soil, facilitated the increase of grain harvest units with 1 ha of crop rotation on the 32% in relation to the unfertilized areas. Replacement of manure in the system of fertilizer of «semipolny» field rotation by by-products provided the increase of the productivity of agricultural cultures on 34 %.